Hukum Waris Adat dan Hukum Waris Islam dalam Perspektif Perbandingan - umransyah alie (Fakultas Hukum Universitas Islam Indonesia, 2004)
Customary legacy law consists of the rule about process to give and to move the heritage from one generation to jointheirs. Customary lefacy law originates from tradition or habit that come from human thingking. Islamic legacy law originates from divine revelation of God that is The Holy Al Qur'an. In Indonesia, Islamic legacy law is some customary legacy law that accommodate as Isiamic Legacy law written in Compilation of Islamic Law.